(untitled) (Verbum. Revista de teologie catolică, 2025)
Mediatio Unionis is the title of a book which the Blessed Edward Poppe (1890–1924), a young Flemish priest, was planning to write but of which we have only a draft.2 Poppe wished for the Church to proclaim Mary’s mediation as a new dogma; it seemed particularly relevant to him following so many inhumane acts of the “Great War.” This, he hoped, would bring about profound spiritual renewal in a world on the way to secularization and dehumanization. Mary’s maternal action is an ever-present concern, but especially in the current context within the Church, and also in the world, where peace among nations and true unity are urgently sought. The article exposes Poppe’s intuition concerning the Virgin Mary’s mediatio, and extends this theological topic by relying on my own recent research in the field of Mariology.